Thai Farmers’ Practices and Organic Farmers’ Awareness in Thailand - ปรุงเจริญ, ประสาน; Angasinha, Asst. Prof. Dr.Chatwarun (Journal of Dhamma for Life, 2024)
This study aimed to 1) examine the powers affecting Thai farmers’ practices and 2) investigate Thai farmers’ shift towards organic farming. As qualitative research, the study utilized literature reviews and in-depth field interviews with key informants from five fields: 1) three groups of key informants from Organic Farmer Networks in Yasothon and Surin Provinces, 2) six groups from the civil society sector, 3) one group of entrepreneurs manufacturing processed rice products, 4) one group of organic rice exporters, and 5) three groups from relevant organizations in the public sector, government officials, and former government officials. In total, in-depth interviews and group discussion with 21 key informants. The study found the following results. First, the power influencing Thai farmers’ practices stems from the use of production power in all aspects of rice farming, including organic farming. Amidst historical changes such as the Green Revolution, state management of rice varieties, and the management of land and water resources, this power is exercised through economic, political, and foreign policies to govern the agricultural sector in Thailand. The government’s use of power in agriculture has significantly impacted farmers by promoting a free market, boosting consumption, and changing to rice varieties from the International Rice Research Institute (IRRI). As a result of governmental reinforcement, Thai farmers have increasingly adopted monoculture farming aimed at export rather than focusing on food demands or the development of knowledge or traditional wisdom in rice farming and agriculture. Furthermore, the government has encouraged the use of chemicals in agriculture rather than fostering a deeper understanding of chemical-free farming. Second, debt and health issues are significant problems that have raised organic farmers’ awareness and prompted them to shift their production practices from chemical to organic farming as a means to address these challenges and find solutions. There are three key factors that contribute to self-reliance and the utilization of environmental resources in organic farming: 1) management of soil, water, and rice varieties, 2) a fair rice market, and 3) farmers’ knowledge. Farmers who possess knowledge in the organic farming system are considered high-quality farmers. Organic farmers are typically knowledgeable, attentive, meticulous, and proficient. This indicates that organic farming not only requires knowledge of both organic and chemical farming but also demands greater attention, particularly concerning health, as chemical farming poses long-term health risks. Despite generating income, farmers often have to allocate their earnings to cover medical expenses. They have become aware that continued reliance on chemical farming leads to cancer which is a primary cause of mortality in their communities. Consequently, organic farming offers a solution to alleviate poverty, reduce health issues due to less chemical exposure, and enhance the ecosystem. Ultimately, organic farming presents a solution for Thai farmers.